Nurse- and midwife-led trials in Australia and New Zealand: Scoping review protocol. Issue 5 (October 2022) - Fish, Jennifer A.; Rickard, Claire M.; Gray, Richard; Middleton, Sandy; Homer, Caroline; Keogh, Samantha; Leslie, Gavin; Nemeh, Fiona; Neville, Stephen; Sharplin, Greg; Whitehead, Lisa; Yates, Patsy; et al.
Abstract: Background: Research led by nurses or midwives has the potential to successfully address current issues in clinical care. High-quality randomised controlled trials are needed to inform evidence-based practice; however, nursing and midwifery research has commonly been nonexperimental. Two connected scoping reviews of nurse- and midwife-led randomised controlled trials within Australia and New Zealand will be conducted to highlight potential research directions and identify resources for future research. Aim: The purpose of the two reviews is to map the number and types of randomised controlled trials led by nurses or midwives within Australia and New Zealand. Methods: The concept of interest is randomised controlled trials with a lead principal investigator holding nursing or midwifery credentials. The lead principal investigator must report an institutional affiliation in Australia or New Zealand, and the trial must recruit at a minimum of one site in Australia or New Zealand. Searches for academic literature will be conducted using Pubmed, Emcare, and Scopus. Sources for grey literature will include the Australian New Zealand Clinical Trials Registry, and grant outcomes published by the National Health and Medical Research Council, Medical Research Future Fund, and Health Research Council of New Zealand. Data analysis and presentation will be conducted separately for each review. Discussion: These reviews will comprehensively map the experimental research activity of nurses and midwives within Australia and New Zealand and highlight potential research directions. From this, strategies to facilitate high quality nurse- and midwife-led trials can be developed, which are vital for informing evidence-based practice.